Pengaruh Model Pembelajaran Inkuiri dengan Teknik Scaffolding terhadap Kemampuan Literasi Sains dan Prestasi Belajar IPA - ni ketut erna muliastrini (Jurnal Ilmiah Sekolah Dasar, 2018)
This study aimed at investigating the effect of inquiry learning model with scaffolding techniques toward ability of science literacy and natural science learning achievement. The design used in this study was using basic pattern Single Factorial Independent Group Design with quasi-experiment type. The sample used was 58 students. The data collected were ability of science literacy and naural science learning achievement. The data were analyzed by using MANOVA used SPSS 17.00 for windows. Research results showed that: First, the ability of science literacy students who were taught by using inquiry learning model with scaffolding techniques was significantly better than students who were taught by using conventional model (F = 19,982; p < 0.05). Second, the natural science achievement of students who were taught by using inquiry learning model with scaffolding techniques was significantly better than students who were taught by using conventional model (F = 13,268; p < 0.05). Third, simultaneously, the ability of science literacy and natural science learning achievement between students who were taught by using inquiry model with scaffolding techniques was significantly better than students who were taught by using conventional model.